Research on Width Optimization of Bearing Coal Pillar Between Roadways Under the Influence of Mining on Both Sides - Linjun Peng; Kaixuan Gong; Manchao He (Applied Sciences)
The rational coal pillar width directly improves the utilization rate of coal resources and the safety of coal mines. Taking Jinjitan Coal Mine as the engineering background, using theoretical analysis and calculation through numerical simulation, the distribution of internal stress field and plastic zone of different widths coal pillars under the influence of mining on one side and mining on both sides is compared and analyzed; the original 20 m coal pillar between 113 working face transportation roadway and auxiliary transportation roadway (i.e., 111 working face air return roadway) in Jinjitan Coal Mine was optimized. The result shows that, compared to the 20 m coal pillar, the distribution of the stress field and plastic zone in the optimized 16 m coal pillar affected by mining on both sides is reasonable; the roadway with the 16 m coal pillar between roadways can maintain its stability. According to the field monitoring results, the rationality of the 16 m coal pillar is verified. The coal pillar optimization scheme proposed in this research improves the utilization rate of coal resources and coal mine safety and provides a reliable reference for the coal pillar optimization with the same engineering background as a coal mine.